PENGARUH PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN LJ. STAR SWALAYAN KEC. WARU KAB. PAMEKASAN - Achmad Jailani; Muhammad Hufron (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACT The purpose of this study to know and analyze Product, Price and Location simultaneously affect the buying decision in LJ. Self-service STAR and Product variables, Price partially effect on buying decision in LJ. The self-service STAR and Location have no partial effect on the buying decision in LJ. STAR self-service. The sampling technique using Accidental sampling is by the sample landing of anyone who by chance meet with the researcher can be used as a sample with the condition that the person who happened to be found suitable as a data source. Data analysis tool used in this research is Multiple Linear Regression Analysis. Based on the results of this study note that the value of Fhitung 36.971> Ftable 3.09 so it can be concluded that Products, Prices and Locations affect simultaneously to the decision to buy in LJ. STAR self-service. As well as Product variables, Price affects partially on buying decision in LJ. The self-service and location STAR has no partial effect on the buying decision in LJ. STAR self-service Keyword : Product, Price, Location and Purchase Decision